Mediamorphosis: the new face of radio broadcasting in the new normal era - Budhi Widi Astuti; Ana Nadhya Abrar; Budi Irawanto (Jurnal Studi Komunikasi, 2024)
‘Mediamorphosis’ is a transformation of communication media caused by complex interactions between perceived needs, competitive and political pressures, and social and technological innovation. The digital revolution that gave birth to media digitalisation is one of the causes of mediamorphosis. Another thing that drives mediamorphosis is the impact of the COVID-19 pandemic that hit Indonesia and other countries in the world. Mediamorphosis is a concept used in this study because it refers to the form of radio broadcasts that have changed and adapted due to the novel COVID-19 virus throughout the world and in Indonesia. The main social regulations by the Indonesian Government have implications for radio broadcasting operations. This study aims to see how local private radio– Radio Elisa FM carries out mediamorphosis which is analysed more specifically using the concept of convergence. The research paradigm used is constructivism with a qualitative approach and case study method. The results of the study show that the mediamorphosis carried out by Radio Elisa produces a new face for Radio Elisa broadcasts as a visual radio in the new normal era.